Uporabnost slikovno preiskovalnih metod pri določanju HPV statusa karcinomov glave in vratu - Jerele, Cene (Onkologija (Ljubljana), 2018)
Head and neck cancer presents a serious health issue and is the sixth most common cancer in the world. With an estimated annual burden of 650,000 incident cases worldwide and approximately 440 incident cases in Slovenia, squamous cell carcinoma accounts for about 90 % of head and neck cancer (2015). In the last few decades, the number of oropharyngeal carcinoma cases has notably increased. The reason lies in the human papillomavirus (HPV) epidemic, with high-risk HPV type 16 being isolated from 40%60 % cases of oropharyngeal squamous cell carcinoma. Patients with HPV-positive HNSCC have a notably higher survival rate as well as better treatment response opposed to their HPV-negative counterparts. Therefore, the evaluation of HPV status in these patients has become the main factor in treatment planning and outcome prediction. The current golden standard for determining the viral aetiology of carcinoma is amplifying viral RNA with PCR. While recent studies indicate that radiographic imaging techniques are useful in determining HPV status, there is not enough evidence for them to be used as the sole method for HPV status determination. However, certain radiographic parameters were proven to be specific for HPV-related carcinomas and can be, when combined with other methods, used for determining HPV status. Primary HPV-positive carcinomas are generally smaller, less metabolically active, cause less necrosis and ulcerations, and have well-defined borders. They are usually found in the tonsillar region and at the base of the tongue. HPV-positive HNSCC presents with more frequent and earlier nodal metastases than HPV-negative HNSCC. HPV-positive HNSCC nodal metastases typically have a cystic appearance.
Keywords: head and neck carcinoma; HPV; human papillomavirus; humani papiloma virus; karcinom glave in vratu; oropharyngeal squamous cell carcinoma; ploščatocelični karcinom orofarinksa; radiographic features; radiographic imaging; radiološke značilnosti; slikovno preiskovalne metode